PERKEMBANGAN KANAL OUD BATAVIA ABAD XVII–XX: TINJAUAN SEJARAH PERKOTAAN - Mulyanto, Heru (Paradigma: Jurnal Kajian Budaya, 2022)
Urban environmental problems such as flooding and water pollution have actually occurred in Jakarta (formerly Batavia) since the Dutch colonial era. Batavia was one of the cities with a myriad of urban planning problems, such as canal flooding which continues to this day. This article was written to find the root of the water problem in Jakarta by reviewing the development of canal construction from the Oud Batavia to the Nieuwe Batavia era. This study was conducted to identify the colonial government’s methods for dealing with flooding and repairing problematic canals. Thus, this research is expected to provide an insight for the current government on ways to deal with flood problems in Jakarta in the contemporary era. Results show that the expansion of settlements from Kota Tua to Weltevreden was also influenced by the dirty canal environment in Oud Batavia. Dirty, sedimentary, and problematic canals were restored, but the old problems persist. Then, Weltevreden was chosen as Ommelanden (expansion area) of Oud Batavia.